New trends in software methodologies, tools and techniques : proceedings of the Thirteenth SoMeT_14 - Fujita, Hamido; Selmat, Ali; Haron, Habibollah (Frontiers in artificial intelligence and applications ;, 2014)
Software is the essential enabling means for science and the new economy. It helps us to create a more reliable, flexible and robust society. But software often falls short of our expectations. Current methodologies, tools, and techniques remain expensive and are not yet sufficiently reliable, while many promising approaches have proved to be no more than case-by-case oriented methods. This book contains extensively reviewed papers from the thirteenth International Conference on New Trends in software Methodology, Tools and Techniques (SoMeT_14), held in Langkawi, Malaysia, in September 2014. T.